دراسة التغير في سعر صرف اليورو بناءاً على سعر المصرف المركزي السوري خلال الفترة (3/1/2011م ولغاية 22/1/2018م). - Mansour, Yomn; Suleiman, Talal; Alhayek, Bassel (Latakia University Journal - Economic and Legal Sciences Series, 2019)
دراسة التغير في سعر صرف اليورو بناءاً على سعر المصرف المركزي السوري خلال الفترة (3/1/2011م ولغاية 22/1/2018م). يمن منصور طلال سليمان باسل الحايك يعتبر التقلب في سلسلة سعر الصرف مقياساً لظاهرة المخاطر وإن التغير والتذبذب الشديد يؤدي إلى ضعف ثقة المواطنين بالعملة المحلية، وبالتالي فإن استقرار سعر الصرف يعكس الاستقرار الاقتصادي والسياسي للبلد. يهدف هذا البحث إلى دراسة تذبذب سعر صرف الليرة السورية مقابل اليورو بموجب نشرة أسعار المركزي السوري خلال فترة الأزمة السورية وهل كانت هذه التذبذبات تتأثر بالصدمات الموجبة أكثر من السالبة وذلك باستخدام نماذج EGARCH، حيث بينت الدراسة أن سعر الصرف المدروس لا يتبع للتوزيع الطبيعي، وهو يتأثر بالأخبار السلبية أكثر من الأخبار الايجابية حيث جاء المنحني البياني ملتو نحو اليمين، كما أن مؤشر التفلطح جاء أقل من 3 وهذا يدل على أنه هنالك تباعد في القيم عن الوسط، أما فيما يخص القيم الموجبة لثوابت المعادلة فهذا يدل على وجود علاقة طردية ما بين العائد على سعر الصرف والمخاطر، وبما أن النموذج الأفضل لتمثيل التذبذب في سعر الصرف وفقاً للاختبارات akaike ، Schwarz، log likelihood هو نموذج GARCH الأسي وبالتالي فإن شدة التذبذب لا تعتمد فقط على سعة الصدمة وإنما على إشارة الصدمة أيضاً، ولقد بينت الدراسة أن قيمة اختبار Akaike جاءت سالبة وهذا يدل على أن كمية المعلومات التي يفقدها النموذج عبر الزمن منخفضة نسبياً، أي يمكن الاعتماد على النتائج التنبؤية لهذا النموذج في الأجلين القصير والمتوسط، وأن سعر الصرف يتجه نحو الثبات في الفترة القادمة على المدى القصير والمتوسط. The fluctuation in the exchange rate series is a measure of the risk phenomenon, and the change and extreme volatility leads to weak citizens’ confidence in the local currency. Therefore, exchange rate stability reflects the economic and political stability of the country. This study aims to study the fluctuation of the Syrian Pound against the Euro according to the Syrian Central Price Index during the period of the Syrian crisis. Were these fluctuations affected by positive shocks more than negative using the EGARCH models? The study showed that the studied exchange rate does not follow the normal distribution. With the negative news more than the positive news, where the curve of the graph converged to the right, and the Flatters index came less than 3 and this indicates that there is a divergence in values ​​from the mean, as for the positive values ​​of the constants equation, this indicates a positive relationship between the return on Price is fast And risk. Since the best model for the oscillation of the exchange rate according to akaike, Schwarz, log likelihood is the exponential GARCH model and therefore the intensity of the oscillation depends not only on the shock capacity but also on the shock signal. The study showed that the value of the Akaike test was negative, However, the amount of information lost by the model over time is relatively low, ie, the predictive results of this model can be relied on in the short and medium term, and the exchange rate is moving towards stability in the short and medium term.